2015
DOI: 10.1021/acs.est.5b01538
|View full text |Cite
|
Sign up to set email alerts
|

Distribution System Water Quality Affects Responses of Opportunistic Pathogen Gene Markers in Household Water Heaters

Abstract: Illustrative distribution system operation and management practices shaped the occurrence and persistence of Legionella spp., nontuberculous mycobacteria (NTM), Pseudomonas aeruginosa, and two amoebae host (Acanthamoeba spp., Vermamoeba vermiformis) gene markers in the effluent of standardized simulated household water heaters (SWHs). The interplay between disinfectant type (chlorine or chloramine), water age (2.3-5.7 days) and materials (polyvinyl chloride (PVC), cement or iron) in upstream simulated distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 57 publications
4
28
0
Order By: Relevance
“…Notably, though Utilities A and B shared the same source water, the chemistries and microbiome compositions of the corresponding rigs were distinct, emphasizing the importance of water treatment and distribution in shaping the building plumbing microbiome. This finding is consistent with a recent lab-scale study, in which water generated from simulated distribution systems representing different pipe materials, disinfectants, and water ages was the dominant influence on the composition of the microbial community and occurrence of OPs in simulated household water heaters, rather than the warm, stagnant environment of the heater itself [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, though Utilities A and B shared the same source water, the chemistries and microbiome compositions of the corresponding rigs were distinct, emphasizing the importance of water treatment and distribution in shaping the building plumbing microbiome. This finding is consistent with a recent lab-scale study, in which water generated from simulated distribution systems representing different pipe materials, disinfectants, and water ages was the dominant influence on the composition of the microbial community and occurrence of OPs in simulated household water heaters, rather than the warm, stagnant environment of the heater itself [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…Distinctive microbial communities in parallel units are likely associated with different pretreatment processes and unit configurations, resulting in variations in physiochemical and biological water properties during treatment processes (i.e., water entering ozone tanks). It has been suggested that upstream water quality can be a major factor governing the downstream microbiomes . The findings in the present study highlighted the possibility of manipulating the drinking water microbiome by optimizing the unit design and operating conditions.…”
Section: Discussionsupporting
confidence: 52%
“…Each SPPR was equipped with either eight pieces of 20 mm × 10 mm cross-sectional PEX (n = 18) or solid copper (n = 18) pipe material. Pipe coupons had been aged in the bottles for six years in prior experiments, described elsewhere [ 8 , 9 , 10 , 27 ], which provided a benefit of well-aged premise plumbing pipe materials and mature biofilms at the start of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, lower LD incidence associated with residential exposure was noted from August 2015 onwards and our sampling during this period revealed undetectable or very low levels of L. pneumophila in residential plumbing [ 1 , 3 ]. While temporal associations between the switch in water supply with reduced levels of chlorine, high levels of iron, elevated temperature for Flint River water, and the resulting outbreak of LD were predictable based on prior work [ 7 , 8 , 9 , 10 ], and duly noted for the Flint outbreak [ 1 , 3 , 5 ], precise patterns of the outbreak in relation to large health care facilities versus residential single family homes are still the subject of scientific and public interest [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%